Assisted Surface-state Recombination of Orange-peel Carbon Nanodots in Various Matrices - Fatimah, Siti; Isnaeni, Isnaeni; Tahir, Dahlang (UI Scholars Hub, 2018)
The contentious origin of the luminescence of carbon nanodots (CDs) has attracted considerable attention. In this work, we synthesized CDs from orange peel by using a microwave-assisted technique. We investigated the optical properties of the synthesized CDs. Moreover, we studied the effect of matrix addition on the optical properties of CDs. We found that matrix addition significantly influences the absorbance and photoluminescence of CDs. Shifts in absorbance peak intensity and emission peak wavelength indicated that the bonding of matrix molecules on the surfaces of the CDs has changed the structures of CDs. This finding is supported by the extended half-life of CDs after matrix addition. Our results will expand researchon the use of CDs as phosphorescent materials.